The Analysis of the Linkages Between Inflation, Exports and Imports, and the Interest Rate on the Exchange Rate in Indonesia in the Year 2010-2019 - Suri, Nurasita Indah; Hayati, Banatul (AFEBI Economic and Finance Review, 2022)
This study aims to analyze the effect of the inflation rate, import-export activities, interest rates simultaneously on fluctuations in the rupiah exchange rate against the US dollar from 2010 to 2019. The method used in this study is the VAR/VECM with the Eviews analysis tool. to see whether there is a long-term or short-term effect between variables. The results of this study all have a positive influence on the rupiah exchange rate against the US dollar and are in accordance with the hypothesis and theory used, but the export activity variable is not in accordance with the hypothesis and theory because of the influence of imports on raw materials to produce export goods. This study also provides an update where the interest rate variable uses the theory of interest rate parity, which states that there is a balance of international interest with domestic interest so that the relationship between interest can affect fluctuations in the rupiah exchange rate against the US dollar and increase incoming capital flows.